Innovation Teaching Technology in ESP groups by activities (Conference Zone, 2022)
English for Specific Purposes (ESP) is taught all over the world in different directions. Since the 60s of the last centuries, when it first started being talked about ESP as a separate direction in teaching English as a foreign language, this aspect of English language teaching has developed considerably and has taken a leading position in teaching English for professional purposes. In the context of the dynamic development process of international integration and exchange of information professionals in any industry, in addition to traditional training, you need a tool that allows you to effectively and efficiently exchange professional information. That tool is a professionally oriented special purpose language or a language.